(untitled) (Altre Modernità, 2024)
Reading Wendy Larson’s Women and Writing in Modern China (1998) to Reflect on Gender-based Approaches in China Studies (Wendy Larson, Women and Writing in Modern China, Stanford, Stanford University Press, 1998, 267 pp. ISBN 0-8047-3151-9) by Daniela Licandro